The Development of the Intelligence Culture Policy in Spain: A Case of Institutional Isomorphism - Cremades Guisado, Álvaro (2022)
Since its creation in 2003, the purpose of the intelligence culture policy has been to raise social awareness about the work and the need for the National Intelligence Centre (CNI). This policy has served as a framework for different actions aimed at promoting greater dialogue between the Spanish intelligence service and civil society, with the policy of promoting the culture of defense as the closest and immediate precedent. This article traces the similarities in the development of both public policies throughout the consultation of primary and secondary sources of public access and also analyzes them through the concept of institutional isomorphism. As the main conclusion, the political culture of intelligence is pointed out as a product of a process of emulation of the practices of institutions that share the same organizational field, as those that were already developed in the field of defense.